An Energy Efficiency Perspective on Rate Adaptation for 802.11 n NIC - Li, Chi-Yu; Cheng, Peng; Lu, Songwu; Wang, Xinbing; Ren, Fengyuan; Wang, Tao (IEEE Transactions on Mobile Computing, 2015)
Rate adaptation (RA) has been traditionally used to achieve high goodput. In this work, we design RA for 802.11n NICs from an energy-efficiency perspective. We show that current MIMO RA algorithms are not energy efficient for NICs despite ensuring high throughput. The fundamental problem is that, the high-throughput setting is not equivalent to the energy-efficient one. Marginal throughput gain may be realized at high energy cost. We then propose EERA and EERA+, two energy-based RA schemes that trade off goodput for energy savings at NICs. EERA applies multidimensional ternary search and simultaneous pruning to speed up its runtime convergence in single-client operations, and uses fair airtime sharing to handle multiple-client operations. EERA+ further searches for multiple, staged rates to yield more energy savings over EERA. Our experiments have confirmed their effectiveness in various scenarios.